Indonesian Press Freedom during the New Order Period (1966-1998) - Yuwono, Ardi Tri; Sebastian, Andi; Clumpers, Pieter-Jan; Basara, Mustafa (International Journal of Media and Communication Research, 2026)
This study examines the dynamics of press freedom in Indonesia during the New Order period (1966–1998) and identifies factors influencing its fluctuations. Using historical methods with a qualitative approach, this research draws on press statistics and literature studies. The New Order government initially established control through mass purges of communist-affiliated press and a strict licensing system. In the early 1970s, the press enjoyed relative openness in criticizing policies, but this ended after the 1974 Malari Incident, which led to twelve media closures. The regime subsequently reinforced control through a corporatist approach and “telephone culture,” which institutionalized self-censorship. The 1980s marked the press’s shift from a tool of struggle to a commercial enterprise, characterized by media conglomerates and Suharto’s family involvement. In the 1990s, press courage reemerged with coverage of the 1991 Santa Cruz Tragedy, while the 1994 banning of Tempo, Editor, and Detik triggered widespread resistance and the birth of the Alliance of Independent Journalists, enabling the press to freely criticize the government by the regime’s end.